(untitled) (Journal of Applied Learning and Teaching, 2022)
This study sets out to examine the level of academic burnout, resilience, and campus connectedness among undergraduates in Singapore. The data were collected from a total of 125 full-time undergraduates (75.6% response rate, 38% females, 62% males) from a public university in Singapore. The instruments used to measure academic burnout, resilience level, and campus connectedness are the Maslach Burnout Inventory-Student Survey (MBI-SS), the Academic Resilience Scale (ARS-30), and the Campus Connectedness Scale (CCS), respectively. The findings show that respondents on the whole had a moderate level of academic burnout, a high level of academic resilience, and campus connectedness. Female students reported a higher level of burnout, a marginally lower resilience level, and a higher level of campus connectedness than their male counterparts though there was no significant difference between the two groups. In addition, the findings indicate that there was no significant difference between the number of years enrolled in the university and the level of academic burnout, resilience level, and campus connectedness level. Further, the findings of this study show that academic burnout was negatively associated with resilience level and campus connectedness, and the resilience level was positively associated with campus connectedness. These findings provide direction for the university to redesign the assessment structure to support a blended learning environment and provide additional support to students facing academic burnout and undue stress from the pandemic.